Exploring the impact of use and non-use value on behavioral intention to purchase organic foods: evidence from a developing country’s context - Mohd Noor, Nor Azila; Mahmudur Rahman, Khandoker (Universiti Teknologi Malaysia, 2016)
A number of determinants have been investigated by past researchers in the framework of theory of planned behavior.In addition to attitude, subjective norm and perceived behavioral control, use and non-use values have been studied by past researchers with inconsistent results.This article is aimed at identifying the impact of ‘use’ and ‘non-use’ values on organic food purchase intention in a developing country’s context like Bangladesh.Some past studies found both the values significant, whereas some studies found only use-values as dominant determinant in the consumer decision making process.The current study is aimed at exploring the impact of both the use and non-use values simultaneously on the purchase intention of organic foods.The study employs the theory of planned behavior as the research framework to investigate the impact of these values on intention.Partial least-square structural equation modeling (PLSSEM) was adopted. Results showed that both the values were significant predictor of purchase intention along with attitude and subjective norm (SN).Perceived behavior control (PBC) appeared to be non significant relationship. Although both the use and non-use values appear to be important in determining consumer intention, use-value carries higher impact compared to non-use value.